2010
DOI: 10.1002/sia.3588
|View full text |Cite
|
Sign up to set email alerts
|

Present State of Development of Laser‐Assisted Wide Angle Three‐Dimensional Atom Probe

Abstract: Three-dimensional atom probe (3DAP) has been developed in our laboratory. In our instrument, the position-sensitive detector with a diameter of 120 mm following a pair of microchannel plates (MCP) was set up at a distance of 110 mm in front of the apex of the sample. Our original preset-type sample stage with a local microelectrode was adopted. The pulse laser, or voltage pulse, was used as a trigger for field evaporation. The pulse width of the laser was 180 fs at a wavelength of 1030 nm. The pulse width of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Atom probe measurement was carried out in the 3DAP developed in our laboratory [6,7]. This instrument is equipped with a femtosecond pulse laser (1064, 532 nm wavelengths, 300 fs duration) and a cryogenerator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atom probe measurement was carried out in the 3DAP developed in our laboratory [6,7]. This instrument is equipped with a femtosecond pulse laser (1064, 532 nm wavelengths, 300 fs duration) and a cryogenerator.…”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, we have developed a wide-angle laserassisted 3DAP equipped with a femtosecond laser [6,7] and we have been studied the mechanism of field evaporation by the laser [8,9]. In our previous studies, we indicated the thermal effect on the field evaporation from the dependence of polarization angle of laser on field evaporation voltages [8] and the dependence of laser power on mass spectra and desorption images at the wavelength of 1064 nm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were characterized by APT using a three-dimensional atom probe instrument developed in our laboratory [10]. The analyses were carried out using pulsed laser with a sample temperature of 70 K, pulse energy of 2.0 nJ, pulse repetition frequency of 5 kHz, wave length of 532 nm, a laser spot size of approximately 20 µm and evaporation rate of 5-10 ions per 100 pulses.…”
Section: Instrumentationmentioning
confidence: 99%
“…To solve these problems, the laser-assisted wide angle 3DAP instrument has been developed in our laboratory [1]. The delay-line PSD (RoentDek DLD120) with a diameter of 120 mm following a pair of microchannel plate (MCP) was fixed at the distance of approximately 110 mm from the specimen apex.…”
Section: Introductionmentioning
confidence: 99%
“…
Laser-assisted wide angle three dimensional atom probe (3DAP) has been developed in our laboratory [1]. In this study, in order to reconstruct three dimensional arrangement of atoms in more detail, the cryogenerator and field ion microscope (FIM) were installed in our 3DAP instrument, and our original preset-type specimen stage was improved.
…”
mentioning
confidence: 99%